Reduction of Coagulation Factor XIII Concentration in Patients with Myocardial Infarction, Cerebral infarction, and other Thromboembolic Disorders - Alkjaersig, Norma; Fletcher, Anthony P.; Lewis, Martin; Ittyerah, Roy (Thrombosis and Haemostasis, 1977)
Coagulation factor XIII and plasma fibrinogen chromatographic assays have been performed serially in patients suffering from acute myocardial and cerebral infarction, and in others with disseminated intravascular coagulation. The findings were compared with 2 groups of “controls”; normal clinically-well subjects and hospitalized patients with cerebral infarction who exhibited minimal, stable, or improving neurological deficits. Substantial depression of factor XIII concentrations developed in the 3 patient groups, together with concomitant significant increases in the proportion and concentration of plasma high molecular weight fibrin(ogen) complexes (HMWFC). An inverse correlation (p<0.05) between coagulation factor XIII concentration and percentage of HMWFC was demonstrated in the early stages of the illness. These findings suggest that depression of coagulation factor XIII concentration in these states, is secondary to extra vascular or intravascular coagulation and may reflect its degree.